2006
DOI: 10.1590/s1516-35982006000500017
|View full text |Cite
|
Sign up to set email alerts
|

Uso de óleo na dieta de eqüinos submetidos ao exercício

Abstract: RESUMO -Objetivou-se com esta pesquisa avaliar, por meio de parâmetros hematofisiológicos, o desempenho atlético de cavalos submetidos a exercícios de média intensidade alimentados com dietas suplementadas com dois níveis de óleo vegetal (250 e 500 g/dia). Foram utilizados 18 eqüinos machos, castrados, sem raça definida, com faixa etária entre 4 e 8 anos de idade e peso corporal de 456±2,90 kg. Os animais foram distribuídos em um delineamento inteiramente aleatório, em um esquema de parcela subdividida no temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
17

Year Published

2010
2010
2014
2014

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
(18 reference statements)
0
6
0
17
Order By: Relevance
“…Body temperature in horses was also influenced by weather variation, promoting higher metabolic distress in horses at the third exercise test, reducing heat loss from the horses, resulting in higher body temperature after exercise, of 39.9 o C. The body temperature of horses only decreased 120 minutes after the test had finished, while in other tests body temperature began to decrease 20 minutes after the tests. Mattos et al, (2006) verified that including soybean oil in the diet reduced body temperature at the end of 2 hours in horses at trot, with values of 39.2 o C.…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…Body temperature in horses was also influenced by weather variation, promoting higher metabolic distress in horses at the third exercise test, reducing heat loss from the horses, resulting in higher body temperature after exercise, of 39.9 o C. The body temperature of horses only decreased 120 minutes after the test had finished, while in other tests body temperature began to decrease 20 minutes after the tests. Mattos et al, (2006) verified that including soybean oil in the diet reduced body temperature at the end of 2 hours in horses at trot, with values of 39.2 o C.…”
Section: Resultsmentioning
confidence: 70%
“…However, Zeyner et al (2002) observed meaningful increase in glucose concentration in equines fed with soybean oil included in diet, at rest, when compared to animals fed diet without oil, with average values of 95.1 and 88.8 mg/dL, respectively, after 390 days of diet intake. Mattos et al (2006) observed that glucose concentrations did not differ meaningfully before exercise among equines consuming diets with 0; 3.1 and 6.8% soybean oil included, for 3 days, but observed meaningfully difference at the end of physical effort, with higher values in equines consuming hyperlipidemic diets.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations